Digital twins for breast cancer treatment – an empirical study on stakeholders’ perspectives on potentials and challenges - Konopik, Jens; Wolf, Larissa; Schöffski, Oliver (Health and Technology, 2023)
With 2.3 million diagnoses and 685,000 deaths annually, breast cancer is the most common cancer in women. The provision of necessary information throughout the whole patient journey is key to minimize the risk of breast cancer, to detect breast cancer as early as possible, and to aid the treatment process. Digital solutions provide abilities to holistically collect, transfer, and sophisticatedly analyze information. Specifically, digital twins in healthcare, as dynamic replicas of human bodies, are promising approaches for monitoring the condition of their patients and predicting tumor developments based on biometric data. However, the acceptance and adoption of such digital twin solutions in healthcare heavily depend on the individual stakeholders of the treatment process. This study aims to identify potentials and challenges of the introduction of digital twins in breast cancer applications from the involved stakeholders’ perspectives.<br
Keywords: Digital Twin; Digital Health; Healthcare 4.0; Breast Cancer; Personalized medicine; Empirical study